Experts’ views on the bank choice determinants according to the ideal Muslims: intrinsic perspective - Ahmad Azrin Adnan (Universiti Kebangsaan Malaysia, 2013)
Until now, a comprehensif and practical guide on muamalat procedures in banking transaction is still limited. This article attempts to discuss the intrinsic construct of the bank choice determinants according to the ideal Muslim. A group of experts who are among the religious figures, practitioners, consultants and academicians were interviewed. Comments were recorded, collated and themes extracted using grounded theory. Four themes emerged, namely halal and haram deliberation,quality consumption, return of maslahah and capability-based consumption.